Artava - A Potent Dignostic Tool In Gynaecology - yadav, Renu; Kapil, Soni; Shukla, Seema (International Research Journal of Ayurveda & Yoga, 2021)
Artava (Menstrual blood) is one of the Upadhatus (secondary tissue) of rasa dhatu (body tissue); which is used to define the menstrual blood or female sex hormones or ovum at different contexts. However, most commonly the term Artava (Menstrual flow) refers the menstrual blood. The color, texture, smell of menstrual blood picturises hormonal status of women. In classic texts, the variation in color, texture, smell of menstrual blood (Artava) and other associated factors are described in detail under the topic of Artava Dushti (menstrual disorder). The endometrium undergoes the great changes during endocrine cycle; thus, the menstrual blood may vary in color and texture which depends upon the factors such as health conditions, hormonal changes and pathological factors. Hence, Artava (visible menstrual blood) is an easy source and important diagnostic tool to make an approach towards diseases. Uterus disorders ranging from benign to malignant tumours as well as endometriosis can cause abnormal menstrual bleeding and are frequently diagnosed through endometrial biopsy. Yet the proteome of menstrual blood is an easily available non-invasive source of endometrial tissue. Classical texts explain types of menstrual disorders hearing Artava Dushti (menstrual disorder). They also describe in details color, texture, specific smell, amount and other associated features like type of pain in details in Vata, Pitta and Kapha Dushti. So, only by observing menstrual blood variation we can find out disease associated with it. Thus, study of Artava (menstrual blood) and Artavadusti (menstrual disorder). according to Ayurveda may be a major diagnostic tool for diagnosis of underlying gynaecological pathology in current gynecology scenario.